Make Investment Scaling-Up Work in Benin : A Macro-Fiscal Analysis - Barhoumi, Karim (Departmental Papers; Departmental Paper ;, 2016)
This paper conducts a systematic growth and fiscal analysis to determine: (1) the growth potential of Benin's ambitious scaling-up of investment, and (2) how the government can generate the necessary fiscal space needed to increase investment without jeopardizing Benin's solid macroeconomic performance.